2021
DOI: 10.1111/hsc.13481
|View full text |Cite
|
Sign up to set email alerts
|

“I've just never done that:” The influence of transitional anxiety on post‐incarceration reentry and reintegration experiences among veterans

Abstract: Military veterans involved in the criminal justice system are a vulnerable subpopulation that has extensive physical and behavioural health treatment needs. Like nonveteran populations, safe and stable housing, employment and social support are critical for veterans returning to society after incarceration. The challenges of social reintegration are immense, and the risk of recidivism is high. The U.S. Department of Veteran Affairs (VA) has developed specific programmes to assist veterans plan for and assist w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…The ability of peers to provide transportation and other logistical support to help secure and prepare documents (e.g., open bank account), comply with legal stipulations for conditions of probation/parole, and troubleshoot challenges when they arose (e.g., inappropriate housing match) was probably also critical, especially during the first days and weeks of reentry. Peers found, as we have noted in a prior publication from this study (Hyde, et al, 2021 ), that the intensity of work coincided with major transitions – such as in housing, employment, and relationships.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The ability of peers to provide transportation and other logistical support to help secure and prepare documents (e.g., open bank account), comply with legal stipulations for conditions of probation/parole, and troubleshoot challenges when they arose (e.g., inappropriate housing match) was probably also critical, especially during the first days and weeks of reentry. Peers found, as we have noted in a prior publication from this study (Hyde, et al, 2021 ), that the intensity of work coincided with major transitions – such as in housing, employment, and relationships.…”
Section: Discussionsupporting
confidence: 84%
“…Lack of health insurance, competing economic needs, residential instability, and unaddressed mental health and substance use needs are significant barriers to accessing health and social services after returning to the community (Mallik-Kane, Paddock and Jannetta, 2018; Marlow et al, 2010;Vail et al, 2017). Less often highlighted are challenges related to inexperience with routine healthcare and negative prior experiences with social services (Hyde et al, 2021), which may in part underlie reasons for limited engagement in physical or behavioral health care in the months following release (Bellamy et al, 2019;Mallik-Kane & Visher, 2008;O'Connell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veterans often struggle with reentry and social reintegration into the civilian sector post-release from the military, particularly with housing and access to mental health care [ 23 ]. All respondents had some experience with homelessness, ranging from three weeks to ten years.…”
Section: Resultsmentioning
confidence: 99%
“…In another qualitative study, people experiencing homelessness were afraid they would return to substance use after release [ 26 ]. Moreover, Hyde et al, found that veterans recently released from prison expressed “transitional anxiety” which accompanied seeking housing and employment [ 39 ]. Participants noted that background checks for employment and educational programs that exclude persons with felony convictions limit options for people with a criminal record.…”
Section: Discussionmentioning
confidence: 99%